Pengetahuan dan Perilaku Seksual Pranikah pada Remaja SMA di Wilayah Kerja Puskesmas Tampaksiring I - Ni Luh Putu Rustiari Dewi; Ida Bagus Wirakusuma (Universitas Udayana, 2017)
The survey conducted by BKKBN in 2012 resulted in 48,1% 15 to 19 year-old women who were pregnant before marriage whichwere caused by free sexual behavior. In 2014 women who were pregnant before marriage were conducted 0,4% by TampaksiringPublic Health Centre I. This study has objective to describe the youth level knowledge and premarital sexual behavior among highschool teenagers at Tampaksiring Public Health Centre I working place. This research was carried out in a descriptive quantitativecross-sectional study. The samples were grade XII students of SMA Amarawati dan SMK Pariwisata Trisakti with a total sample of123 persons that attended filling the questionnaires, but 15 persons didn’t fill the whole questionnaires which exclude from thesample. Data was collected using questionnaires. 48,1% of 108 respondents had inadequate knowledge level mainly knowledgeabout sexual behavior, only 38% of children answered correctly. The number of childen who had a relationship of 90.7% withsexual behavior most was hugging and kissing the cheek of 81% and sexual intercourse were 11 children (10.2%).